ANALISIS FAKTOR YANG MEMPENGARUHI KETIMPANGAN DISTRIBUSI PENDAPATAN PROVINSI DIY TAHUN 2012-2023 DENGAN PENDEKATAN MODEL MIXED EFFECT - Faranisa, Ariadna Aqila; Pertiwi, Angelita Titis; Kawuryan, Istiarsi Saptuti Sri; Fevriera, Sotya (Badung Bali: Politeknik Negeri Bali, 2025)
The outcomes of development in each region depend on the endowment and management of the area. The differences of development outcomes cause the phenomenon of inequality in income distribution, which can be conceptually observed and measured by the Gini index. This study aims to analyze the influence of the Human Development Index (HDI), the Open Unemployment Rate (OUR), and the Regional Minimum Wage (RMW) on income distribution inequality in the Special Region of Yogyakarta (DIY) Province for the period 2012-2023. This research employs panel data analysis with a mixed effect model and uses Stata 14 as the analytical tool. The study demonstrates that the HDI and OUR variables have a positive and significant impact on income distribution inequality, whereas the RMW variable does not have a significant effect on income distribution inequality in DIY from 2012 to 2023. Although the Gini index in DIY Province is relatively low, the results of the mixed effect model indicate significant inequality across its regencies/ cities. The local government of DIY and other related stakeholders should ensure that education, healthcare, and employment are accessible for all people in DIY.